A Pilot Study of Ion - Molecule Reactions at Temperatures Relevant to the Atmosphere of Titan - Zymak, Illia; Žabka, Ján; Polášek, Miroslav; Španěl, Patrik; Smith, David (Origins of life and evolution of the biosphere, 2016)
Reliable theoretical models of the chemical kinetics of the ionosphere of Saturn's moon, Titan, is highly dependent on the precision of the rates of the reactions of ambient ions with hydrocarbon molecules at relevant temperatures. A Variable Temperature Selected Ions Flow Tube technique, which has been developed primarily to study these reactions at temperatures within the range of 200-330 K, is briefly described. The flow tube temperature regulation system and the thermalisation of ions are also discussed. Preliminary studies of two reactions have been carried out to check the reliability and efficacy of kinetics measurements: (i) Rate constants of the reaction of CH3+ ions with molecular oxygen were measured at different temperatures, which indicate values in agreement with previous ion cyclotron resonance measurements ostensibly made at 300 K. (ii) Formation of CH3+ ions in the reaction of N2+ ions with CH4 molecules were studied at temperatures within the range 240-310 K which showed a small but statistically significant decrease of the ratio of product CH3+ ions to reactant N2+ ions with reaction temperature.
Keywords: Temperature; Titan ionosphere; Models, Chemical; Extraterrestrial Environment; pilotní projekty; VT-SIFT; Variable Temperature Selected Ions Flow Tube; Ion-molecule reactions; mimozemské prostředí; Saturn; kinetika; atmosféra; ionty; teplota; Pilot Projects; Atmosphere; Ions; chemické modely; CH3 + ions; Kinetics